2006
DOI: 10.2214/ajr.05.0216
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of the Coronary Arteries: Feasibility of Low-Dose CT with ECG-Pulsed Tube Current Modulation to Reduce Radiation Dose

Abstract: This study showed the combined effect of lowering the kilovoltage setting (80 kV) and using an automatic modulation technique (ECG-pulsed tube current modulation) for coronary CT. Radiation dose exposure can be reduced by up to 88% for slim patients without impairing image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(133 citation statements)
references
References 11 publications
2
126
2
2
Order By: Relevance
“…44 Additionally, with the advent of new MDCT technology, the radiation dose for CTA could be minimized to the level of background radiation (Ͻ3 mSv). 45 Our study has several limitations. This analysis is one of a cross-sectional nature, so it is not possible to make causal inferences.…”
Section: Discussionmentioning
confidence: 91%
“…44 Additionally, with the advent of new MDCT technology, the radiation dose for CTA could be minimized to the level of background radiation (Ͻ3 mSv). 45 Our study has several limitations. This analysis is one of a cross-sectional nature, so it is not possible to make causal inferences.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that lower tube voltages considerably reduce the radiation dose of CT examinations [11,36,37]. For CS, this relevant dose reduction is possible without compromising the reproducibility and accuracy of the method.…”
Section: Discussionmentioning
confidence: 99%
“…In order to keep radiation exposure as low as reasonably achievable (ALARA), recent modifications of multi-slice CT scanning protocols have been implemented, such as the use of a low tube current [8,9], attenuation-based tube current modulation [10], and use of low tube voltage protocols [11,12]. In general, two modes of phase synchronization have been traditionally used, i.e., the retrospective electrocardiography (ECG)-gating technique [13,14] that acquires continuous data in a helical (spiral) mode and the prospective ECGtriggering technique [15,16] that obtains data at predefined time points of the cardiac cycle in an axial step-and-shoot mode, the latter usually being associated with a lower radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…25 • With correct dose reduction strategies in slim patients, the dose can be reduced by up to 88% with no reduction in image quality. 26 The use of prospective gating may deliver doses as low as 1mSv. 27 • Nevertheless, a recent study (proposing a more appropriate dosecorrection factor) concluded that CTCA could be associated with a higher dose than previously thought.…”
Section: Calcium Scorementioning
confidence: 99%